Examining Hepatitis C Virus Treatment Preference Heterogeneity Using Segmentation Analysis: Treat Now or Defer?. Issue 3 (March 2016) - Fraenkel, Liana; Lim, Joseph; Garcia-Tsao, Guadalupe; Reyna, Valerie; Monto, Alexander
Abstract : Objective: To improve our understanding of patients' treatment preferences for chronic hepatitis C (HCV). Methods: Subjects with HCV were recruited from 2 VA medical centers. Preferences were ascertained using conjoint analysis. We used segmentation analysis to examine whether there were groups of respondents with similar preferences that were systematically different from the preferences of others. We then measured the associations between treatment preference with subjects' characteristics and their gist principles related to living with HCV and the burden of therapy. Results: A total of 199 subjects participated in this study. The segmentation analysis demonstrated that subjects could be classified into 2 distinct groups. The larger group [group 1, n=118 (59%)] opted for current treatment and the other [group 2, n=81 (41%)] preferred to defer. Patients with cirrhosis were less likely to belong to group 2 (prefer to defer) compared with those without cirrhosis (40.5% vs. 21.3%), whereas subjects self-identifying as African American were more likely to belong to group 2 than white subjects (51.3% vs. 30.5%). Members of group 1 had a more positive overall gist principles related to HCV compared with members of group 2 [mean (SD) score=28.63 (3.06) vs. 26.46 (2.79), P <0.0001]. These gist principles mediated the relationship between race and treatment preference (Sobel test statistic=−2.68, 2-tailed P =0.007). Conclusions: Our findings indicate that there are groups of HCV patients with similar preferences that are distinct from other groups' preferences. Patients' gist principles related to the significance of having a chronic viral infection and the burdens of therapy are strongly related to their current treatment decisions. These findings help inform how best to initiate and deliver treatment for patients with HCV. Abstract : Supplemental Digital Content is available in the text.